Should patients still be copied into their letters? A rapid review. Issue 12 (December 2018) - Harris, Emma; Rob, Priyanka; Underwood, Janet; Knapp, Peter; Astin, Felicity
Highlights: Little is known about copy letter content and its effect on health outcomes. Most, but not all, patients find copy letters useful and understandable. Health literacy levels of participants in included studies are largely unknown. The reading level of 51, 379 copy letters ranged from "standard" to "difficult". Medication lists in copy letters sometimes contain errors and omit lifestyle advice. Abstract: Objective: To systematically identify, synthesise and evaluate the strength of the international evidence on copy letter practice. Methods: A systematic search identified original research studies on copy letters. Searches were limited by date and language as permitted in rapid review methods guidance. Article screening, data extraction and strength of evidence assessment were completed independently by multiple authors. Results: Thirty-seven studies were included. There was a lack of information about copy letter content. Many patients report being satisfied with copy letters, understand them and find them useful. However, there is a lack of objective, high quality evidence to suggest that copy letters increased patient understanding or improved physical or psychological health outcomes. Many letters were written at a level which would make them inaccessible to patients with low health literacy. The strength of evidence was either "emerging" or "acceptable" practice for most studies (n = 30). Conclusion: There is a lack of objective, high quality evidence to demonstrate the benefits of copy letters as described in health policy. Practice Implications: Personalising letters and using lay rather than medical terms appears to be useful for improving copy letter readability. Further research is required to explore this, especially in people with low health literacy levels.